Onegin ebook English and russian language edition. - Pushkin, Alexander (World Classics., 2015)
Bilingual edition of Pushkin's Eugene Onegin in both Russian and English languages. Meet Onegin, a dandy from Saint Petersburg, about 26. An arrogant, selfish and world-weary cynic. One day he inherits a landed estate from his uncle where he strikes up a friendship with his neighbour, a starry-eyed young poet named Vladimir Lensky. One day, Lensky takes Onegin to dine with the family of his fiancee, the sociable but rather thoughtless Olga Larina. At this meeting he also catches a glimpse of Olga's sister Tatyana. A quiet, precocious romantic and the exact opposite of Olga, Tatyana becomes intensely drawn to Onegin. Soon after, she bares her soul to Onegin in a letter professing her love.